Analisis Efisiensi Pengajaran Project Based Learning Pada Praktikum Pipa Organa Sederhana - Oktapiani, Rahma Amelia; Hamdie, Haifina Nuzha Nairiza; Damayanti, Febriana Eka (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
The learning process in physics requires media as illustrations to be able to apply concepts so that they are easier to understand. This method is also useful for an educator to be able to analyze the learning abilities of each student, however, regarding the concepts of vibration, sound waves and frequencies, there are still many errors in understanding and in organ pipe material not many applications of this media have been implemented. so that researchers make media from glass bottles using the project based learning method in implementation with the aim of students being able to understand the concept of vibrations, sound waves and frequencies further, knowing how they work or the principles used and, being able to analyze the factors that influence the speed of wave propagation and frequency. resulting from. From this research, it was found that the wavelengths for each bottle from 1 to 7 were 5.86, 5.07, 4.92, 4.72, 4.30, 3.95 and the resonance frequencies were 58.02, 134.12, 207. .31, 288.13, 375.27, 474.41, 602, 53.